Creating a culture of family planning in youth and adolescents - Татарчук, Т. Ф; Силина, Н. К.; Шкиряк-Нижник, З. А.; Силина, Т. Н.; Яроцкая, Н. В. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
Education of young women and girl-teenagers the methods of family planning with convenient, obtainable and safe contraceptive methods is a key strategy of improving maternal and infant loss. Using of combined oral contraceptives (COCs) in Ukraine among teenagers is limited by the cost of drugs. One of ways to solve the problem of availability of COCs with contraceptive purpose, as well as dysmenorrhea, hypermenorrhea to girls is to use a generic drug Zhastinda®, containing dienogest 2,0 mg and ethinylestradiol 0,03 mg.